Our surgical experiences on vascular injuries in Afrin Olive Branch operation - Özgüler, İbrahim Murat; Atlı, Fahri Hayri; Kılıç, Ahmet Turhan; Güzel, Gökalp; Köşker, Taylan Özgür (My University, 2019)
Objectives: In this study, we present our surgical experiences on vascular injuries during the Afrin Olive Branch operation of Turkey.Patients and methods: Between February 2018 and May 2018, a total of 37 traumatized patients (36 males, 1 females; mean age 26.8 years;range, 17 to 55 years) with vascular injuries who were treated by cardiovascular surgeons during the Afrin Olive Branch operation wereincluded in this study.Results: A total of 37 patients underwent 46 vascular surgical procedures. There were no surgery-related mortalities during follow-up.Twenty patients (54%) were discharged and 17 patients (46%) were transferred to an external center in the postoperative early period.Conclusion: Based on our experiences, we suggest that major arterial injuries should be repaired rather than direct amputation, and thesaphenous vein must be used for bypass or interposition, where applicable.
Keywords: Periferik Damar Hastalıkları; Genel ve Dahili Tıp; Acil Tıp; Cerrahi